Enhanced sensitivity subwavelength grating waveguides for silicon photonics sensing applications - Wanguemert-Pérez, Juan Gonzalo; Hadij-El-Houati, Abdelfettah; Sánchez-Postigo, Alejandro; Leuermann, Jonas; Pereira-Martín, Daniel; Luque-González, José Manuel; Cheben, Pavel; Xu, Dan-Xia; Schmid, Jens H.; Ctyroky, Jiri; Soler-Penades, Jordi; Nedeljkovic, Milos; et al. (My University, 2019)
In this work we will review the enormous potential of subwavelength grating waveguides for sensing applications in the near and mid-infrared bands, demonstrating the capability to engineer the mode profile to maximize the light-matter interaction.
OSA (Optical Society of America)
Keywords: Sensores ópticos; Congresos y conferencias; Subwavelength grating metamaterial waveguides; Sensing applications; Light-matter interaction; Near infrared band; Mid-infrared band